Pelaksanaan Perjanjian Kerja Waktu Tertentu di Cv Febrio Garmen Denpasar - Cynthia Febriani; Ni Luh Mahendrawati; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2019)
Abstract Work agreements bring problems, for companies that have different problems. Problems that occur General entrepreneurs will always be strong parties and temporary workers on the weak side. Power differences caused by